Danse Macabre, Piano Quintet for piano left-hand, violin, viola, cello, and clarinet - Boondiskulchok, Prach (2023)
Reviewed by the Edition boardCommissioned by the Wittgenstein Project, supported by Fonds Podium Kunsten NederlandWorld premiere: Antonii Baryshevski (piano), Lars Wouters van den Oudenweijers (clarinet), Prisma Strijktrio – Janeke van Prooijen (violin), Elisabeth Smalt (viola), Michiel Weidner (cello), Stadsgehoorzaal, Leiden, Netherlands, 27 January 2024
This piano quintet follows a long musical tradition of compositions inspired by the Danse Macabre, a theme prevalent in 15th-century art, skeletons are depicted dancing alongside characters from every societal rank, an allegory of death’s universality.The idea of a Danse Macabre as a theme fitting for a left-handed-piano-quintet came to me accidentally: one unremarkable night, having slept on my right arm until it went numb, moving it produced a strange sense that it was not my arm—a kind of “phantom limb” experience (or perhaps the reverse). The metaphor of the “phantom” seemed to me to tie together many disparate ideas related the story of the left-handed-pianist: invisibility, disability, extreme virtuosity, the “forgotten” hand, and ultimately a sort of memento mori.The piece’s structure follows the common medieval depiction as shown in the image above (John of Kastav, Holy Trinity Church in Hrastovlje, Slovenia). Here Death, manifested as skeletons, dances with earthly characters one by one. In this piece, Death is represented by bells (an homage to Henri Cazalis’s poem, that in turn inspired the most popular of all Danses Macabres by Saint-Saëns) followed by a somewhat grotesque attempt to dance. In between each manifestation of this, there are six tableaux of living beings: the princess, the beggar, the patriot, the very busy, the dreamer, and the child. While we can very well imagine these six as medieval characters, we also know them well as contemporary stereotypes. The final tableau, a waltz, sees materials from each of the characters dancing all together, on a thin line between joy and denial, between beauty and banality.
FRIS
Editorial review
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850